Research on the spatial layout optimization strategy of Huaihe Road Commercial Block in Hefei city based on space syntax theory - Zhou, Qinghua; Zheng, Yiran (Frontiers in Computational Neuroscience, 2023)
Commercial block not only serves as a public space for the consumption, entertainment and recreation of residents but also witnesses the history of urban commercial development. With the urban development and the improvement of people’s living standards, most commercial blocks are faced with such problems as traffic congestion, simple commercial form and unreasonable spatial layout. By taking the commercial block of Huaihe Commercial Pedestrian Street as an example and combining the axis and viewshed analysis method of space syntax theory, this paper has analyzed the spatial layout of commercial blocks and wrapped up the strategies for optimizing the spatial layout of commercial blocks, hoping to facilitate the spatial layout of commercial blocks.